Increasing creativity in design education: measuring the e/affect of cognitive exercises on student creativity - Merrill, Jeremy (Kansas State University, 2013)
Creativity is vital to the design professions although there is a not a common understanding among designers about the nature of creativity. Designers need a model of creativity that helps place the importance of creativity in the design process and informs educators about how to better enhance creativity in their students. Merrill’s Model of Creativity in Design (Merrill & Rolley 2012) was developed by the researcher and served as the framework for exploring the effect of an academic intervention on the creativity of college freshman design students in order to answer the question: Does participating in an academic intervention affect the creativity of first-year, three-dimensional design students, as measured by the Figural Torrance Test of Creative Thinking? A mixed methods approach allowed development of a rich field of data for analysis as well as a body of student work and experiences. Design students were taught creativity techniques in addition to completing short exercises during a one-hour weekly seminar class, Design Thinking and Creativity. These students were compared to a control group of students utilizing a modified Solomon four-group non-equivalent control group quasi-experimental research design, adapted from Campbell and Stanley (1966). A paired t-test compared post-test scores between the treatment group (n=70) and the control group (n= 18). Qualitative data was also collected including a demographic survey, a Creative Self-Assessment, and interviews. The treatment group, on average, (M=113.53, SE=1.82) scored significantly higher than the control group on the post-test administration of the FTTCT (M=104.78, SE=3.41), t(84)=-2.22, p<.05, r=.06). An analysis using Spearman’s Rho determined a significant correlation between individual participant’s scores on three assessments of individual student creativity, which focused on the individual’s creative cognitive abilities; however, there was no significant correlation with the final creativity project. These findings show that deliberate creativity education coupled with creativity exercises allowed students to slightly raise their creativity while the creativity of their peers dropped. Analysis of qualitative data revealed high student confidence and commonalities in defining creativity. This study demonstrates that an academic intervention can improve the creativity of beginning design students and provides a theoretical framework for future creativity research and teaching.
Keywords: Creativity; Design education; Design (0389); Higher Education (0745)